2022
DOI: 10.1039/d1re00488c
|View full text |Cite
|
Sign up to set email alerts
|

Solvent-free liquid-phase selective catalytic oxidation of toluene to benzyl alcohol and benzaldehyde over CeO2–MnOx composite oxides

Abstract: An efficient method for highly selective preparation of the high value-added benzyl alcohol (BOL) and benzaldehyde (BAL) from liquid-phase catalytic oxidation of toluene with molecular oxygen over CeO2-MnOx composite oxides...

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
4
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 16 publications
(5 citation statements)
references
References 69 publications
1
4
0
Order By: Relevance
“…The characteristic peaks at 642.1 and 640.7 eV are ascribed to the existence of Mn 3+ and Mn 2+ , respectively. [1] The result of Mn 2p XPS spectra further accurately reveals the oxidation state of Mn species, and this finding is consistent with the result of XRD.…”
Section: Catalyst Characterization Analysissupporting
confidence: 84%
See 2 more Smart Citations
“…The characteristic peaks at 642.1 and 640.7 eV are ascribed to the existence of Mn 3+ and Mn 2+ , respectively. [1] The result of Mn 2p XPS spectra further accurately reveals the oxidation state of Mn species, and this finding is consistent with the result of XRD.…”
Section: Catalyst Characterization Analysissupporting
confidence: 84%
“…[ 15 ] In Chen's group, they demonstrated a CeO 2 ‐MnO x solvent‐free catalytic system with oxygen as an oxidant, and the conversion of toluene and the selectivity to BOL and BAL were 6.9% and 64.4%, respectively. [ 1 ] It is easily seen that Mn‐ and Co‐based catalysts are mostly used as metal‐based catalysts for the catalytic oxidation of toluene. Reddy et al and Xia et al reported MnO x /γ‐Al 2 O 3 catalyst and Mn/g‐C 3 N 4 /ZSM‐4 to apply for the total oxidation of toluene.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Chen et al 95 demonstrated that CeO 2 –MnO x composite oxides displayed good selectivity towards benzyl alcohol and benzyl aldehyde (Fig. 8d).…”
Section: Sustainable Synthesis Of Value-added Chemicalsmentioning
confidence: 94%
“…At present, as an economical and environmental oxidant, O 2 is used for the oxidation of toluene. 8–11 But its reaction conditions are harsh (usually high temperature and pressure), and the conversion rate of toluene is low, so oxidation of toluene remains a challenge with mild conditions. Although noble metals have higher efficiency for toluene oxidation, such as Pt, 12 Pd, 13 and Au, 14 large-scale applications are limited due to the high cost and scarcity of these catalysts.…”
Section: Introductionmentioning
confidence: 99%